Peran Badan Kerjasama Antar Desa Dalam Perlindungan, Pengelolaan, Pelestarian Hasil Pelaksanaan Program Nasional Pemberdayaan Masyarakat Mandiri Kabupaten Jember - Kamilia Ustman; Supranoto Supranoto (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2019)
There are several roles undertaken by the Inter-Village Cooperation Agency (BKAD) after the decommissioning of the National Community Empowerment Program (PNPM) by the central government and the emergence of Bupati Regulation Number 20 Year 2015, relating to the Protection, Management and Preservation of PNPM Implementation. Overall protection, management and conservation companies are efforts made to provide legal guarantees, maintain sustainability, and expand the results of participatory development carried out by PNPM in the form of SPP (savings and loans for women) and distribution of facilities. The problem faced by BKAD is the ongoing arrears that are ongoing from the SPP group in Jombang. This research takes issue by investigating the role of BKAD in protecting, managing and preserving the results of PNPM implementation in Jombang. Qualitative descriptive was chosen to examine the problem being investigated. Research data were collected by in-depth interviews, observation, and documentation. Determination of informants was done by purposive sampling and snowball sampling. Data was validated through consistent participation, observation, member checking, and triangulation. Data were analyzed qualitatively, which consisted of data collection, data reduction, data presentation, and data verification. Research findings cover four problems. First, BKAD made protective efforts aimed at inventory of SPP assets and property through discussion. Secondly, BKAD conducts a management program by restructuring client loans, in collaboration with all teams involved in PNPM. Third, conservation efforts undertaken by BKAD produce sustainable SPP. Some difficulties were seen in the management phase, related to SPP arrears.